PENINGKATAN KEMAMPUAN GURU-GURU KIMIA KABUPATEN KENDAL DALAM MENDESAIN PENELITIAN TINDAKAN KELAS - Saptorini, Saptorini; Widodo, A Tri; Kadarwati, Sri (Jurnal Penelitian Pendidikan, 2013)
The results of preliminary study showed that chemistry teachers in Kendal didn’t know how to design CAR, has not been able to integrate models, strategies, and approaches of learning to certain topics to design CAR, and find the time management difficult in CAR. Thus, it was needed to train them the basic skills to teach so they will be able to design and conduct a CAR that will give a direct impact on the quality instuction in the classroom. This activity was carried out in two main phases, namely seminar and workshop in stage I and mentoring of CAR preparation in stage II. The results of this activity indicated that CAR preparation training for chemistry teachers in Kendal was be able to improve chemistry teachers’ capability in developing CAR. However, an increase in teachers’ character as a figure, in addition to increasing the professionalism of teachers who simply boils down to the academic side is still needed. In addition, the school and the Education Department needs to provide more facilities for the implementation of CAR in school continue to increase the sustainaible quality of the learning process.